Catechesis of Technology: The Short Life of American Technical Catechism Genre 1884–1926? - Brockmann, R. John (Journal of Technical Writing and Communication, 2014)
Between 1884 and 1926, such publishers of technological information as Henley Publishing, Audel Publishing, John Wiley, Van Nostrand, McGraw-Hill, and Practical Publications put out dozens and dozens of technical catechisms on a wide variety of technical subjects. Then, around 1926, these publishers ceased releasing texts called catechisms. What made the genre so popular? Did it disappear? The answers to these questions provide a case study of genre adaptation, genre change, and genre persistence within technical communication.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMjE5MC90dy40NC4yLmI